Association of classic cardiovascular risk factors with myocardial infarction and ischemic stroke: A cross sectional analysis of the Shiraz Heart Study - Haleh Ghaem; Mohammad Javad Zibaeenezhad; Mehrab Sayadi; Sheida Khosravaniardakani; Nader Parsa; Iman Razeghian-Jahromi (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: Myocardial infarction (MI) and ischemic stroke are the leading deadly clinical outcomes globally. This study aimed to investigate the association of classic cardiovascular risk factors with MI and ischemic stroke in a general population. Methods: This cross-sectional study used the baseline data of the Shiraz Heart Study, a prospective cohort that investigate risk factors of coronary heart disease in a general population of Iran. Middle-aged citizens of 40–70 years old were included. Univariable and multivariable logistic regression analysis was performed to explore the association between sociodemographic, clinical, and metabolic factors and prevalent MI and stroke. Results: Out of 7225 adults, 1.9 % (n = 135) had prior MI or stroke. Multiple logistic regression revealed that age≥60 years (aOR: 2.22, 95 % CI 1.45–3.20; P < 0.001), male sex (aOR: 3.82, 95 % CI 2.56–5.71; P < 0.001), history of hypertension (aOR: 1.71, 95 % CI 1.18–2.50; P < 0.005), history of hyperlipidemia (aOR: 2.42, 95 % CI 1.68–3.48; P < 0.001), having four 1st degree family members with sudden cardiac death (aOR: 26.28, 95 % CI 0.59–432.09; P < 0.022), and having a 1st degree family member with history of cardiovascular disease (aOR: 1.69, 95 % CI 1.13–2.54; P < 0.001) were associated with prior MI and stroke. Unlike high-density lipoprotein (P = 0.723) and triglyceride (P = 0.643), there were significant differences in the levels of fasting blood sugar (P < 0.001), total cholesterol (P < 0.001), and low-density lipoprotein (P < 0.001) between those with and without history of MI/stroke. Conclusions: Being aged ≥60 years, history of hypertension and hyperlipidemia along with familial history of CVD and sudden cardiac death were in association with MI and stroke.